Tomada de decisão no uso de aeroportos regionais para o escoamento da produção da agricultura familiar em sua área de influência: um enfoque metodológico aplicado ao caso do aeroporto de Aracati-Ceará - Maciel Filho, José Ari Cosme de Lima (2013)
Choice of transport mode by actors of any supply chain in Agriculture sector is a very important decision to provide speed as well as to increase competitivity and quality of its products. It is known that a way a product is transported plays a strategic role in commerce and in the operations of productive chains. Air transport mode has been supporting regional development as it increases speed, reliability and safety to markets which aim competitive advantages. This transport mode must be understood as a system composed of several interacting components while attending worldwide markets. To have transport mode available in regional space it is firstly necessary knowing local transport demands through an effective planning of regional air transport sector. This is crucial because one needs to know the necessities of both passenger and cargo transport to set up priorities in attending demands as well as in put forward policies which aggregate value to transport activity. The present study aims to help decision making in planning and operating regional airports in their roles as regional production flowing portal. A case study was considered involving the airport of Aracati, county located in State of Ceará, in the northeastern Brazil. System Analysis concepts and the Analytic Hierarchical Process (AHP) tecnique were employed to search for operating problems in attending demand and to elicit necessities and preferences of potential airport customers. Structured questionnaires were applied to people in charge in Aracati Airport management and other public authorities as well as in agricultural cooperatives in the study region. So, it was possible to anticipate problems and to elicit from airport potential customers their preferences concerning five points: costs, accessibility, safety, cycle time and available land infrastructure. Consequently, an Action Plan was devised to contribute to decision making both in public and private sectors trying to reinforce the airport role in supporting import/export regional activities. Finally, it is important to mention that the Aracati Airport has enough area to build a Cargo Terminal but the necessary investments need a feasibility study and actions involving conjoint efforts of regional producers and their associations, entrepreneurs who will be operating in the airport, suppliers of the regional productive chain and public authorities.